Integrated Family Approach in Mental Health Care by Professionals From Adult and Child Mental Health Services: A Qualitative Study - Stolper, Hanna; van Doesum, Karin; Steketee, Majone (Frontiers in Psychiatry, 2022)
Objective A multiple case-study in which each case was evaluated by adult and child mental health professionals who used an integrated family approach in their treatments. In this approach, treatment focuses on the mental disorders of the parents as well as on the development of the young child and family relationships. This study evaluated the experiences of professionals from adult and child mental health services using this approach. The aim of the study is identifying key elements of this approach, processes involved in treatment, and barriers to its success, with the aim of contributing to the development of practice based integrated mental health care for the whole family. Background Parental mental disorders have an impact on parenting and child development. To stop detrimental cascade effects and prevent parent and child from being caught up in the intergenerational transmission of psychopathology, an integrated family approach in mental health care is needed. Methods: A qualitative case study design using a grounded theory approach. Data were collected through 19 group interviews of professionals (N = 37) from adult and infant mental health teams who worked together in the treatment of a family. Results Professionals from the two services were comfortable coping with complexity and felt supported to perform their treatments by staying in touch with each other in multi-disciplinary consultations. They indicated that by attuning the treatment components to each other and tailoring them to the capabilities of the family, their treatments had more impact. A flexible attitude of all involved professionals and commitment to the interest of all family members was essential. Conclusion According to professionals, treatment with an integrated family approach in mental health care is of value for families by addressing the distinct roles, positions and relationships, by implementing a flexible complementary treatment plan, and by empowering professionals by multi-disciplinary consultations.